Coordinated tissue-specific regulation of adjacent alternative 3′ splice sites in C. elegans - Ragle, James Matthew; Katzman, Sol; Akers, Taylor F.; Barberan-Soler, Sergio; Zahler, Alan M.

(untitled) (Genome Research, 2015)
Adjacent alternative 3′ splice sites, those separated by ≤18 nucleotides, provide a unique problem in the study of alternative splicing regulation; there is overlap of the cis-elements that define the adjacent sites. Identification of the intron's 3′ end depends upon sequence elements that define the branchpoint, polypyrimidine tract, and terminal AG dinucleotide. Starting with RNA-seq data from germline-enriched and somatic cell-enriched Caenorhabditis elegans samples, we identify hundreds of introns with adjacent alternative 3′ splice sites. We identify 203 events that undergo tissue-specific alternative splicing. For these, the regulation is monodirectional, with somatic cells preferring to splice at the distal 3′ splice site (furthest from the 5′ end of the intron) and germline cells showing a distinct shift toward usage of the adjacent proximal 3′ splice site (closer to the 5′ end of the intron). Splicing patterns in somatic cells follow C. elegans consensus rules of 3′ splice site definition; a short stretch of pyrimidines preceding an AG dinucleotide. Splicing in germline cells occurs at proximal 3′ splice sites that lack a preceding polypyrimidine tract, and in three instances the germline-specific site lacks the AG dinucleotide. We provide evidence that use of germline-specific proximal 3′ splice sites is conserved across Caenorhabditis species. We propose that there are differences between germline and somatic cells in the way that the basal splicing machinery functions to determine the intron terminus.